A popularity based caching strategy for the future Internet - Hassan, Suhaidi; Din, Ikram Ud; Habbal, Adib M. Monzer; Zakaria, Nur Haryani (2016)
Information-Centric Networking (ICN) is an attractive network model receiving increasing consideration by the research community because of its inspiring features. To better manage the Internet usage move from host-centric communication to receiver-driven content retrieval, revolutionary ICN architectures have been proposed. A distinguished characteristic of these innovative architectures is to provide ubiquitous and transparent in-network caching to enhance network resource utilization and accelerate content dissemination. With the exponential increase of Internet traffic, the issue of content storage is a growing concern in ICN. In this paper, we present a caching strategy that considerably increases cache hit rate and reduces stretch ratio, which are the most important metrics in the evaluation of ICN caching. Through extensive simulations, it is shown that our proposed work is a favorable and realistic contribution for the standardization exercise of data caching for achieving accurate and valid network performance in the future Internet.